Regenerative Pain Therapy Using Platelet-Rich Plasma Compared with Steroid Injection for Spinal Disc Herniation: A Meta-Analysis - Alfan Rizki Nur Rohman; Taufiq Agus Siswagama; Probo Yudha Pratama Putra (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2025)
Background: Radicular pain resulting from spinal conditions remains one of the most challenging problems for clinicians. This meta-analysis aimed to compare the interventional pain outcomes of platelet-rich plasma (PRP) injection versus steroid injection in patients with disc herniation.Methods: A systematic review was conducted following PRISMA guidelines using PubMed, Science Direct, Cochrane Library, and RevMan 5.3. Three RCTs were analyzed.Results: A total of 204 patients were included (PRP n = 101; control n = 103). There was no significant difference between the PRP and steroid for VAS (Visual Analog Scale), ODI (Oswestry Disability Index), and SF-36 scores at 3 and 6 months.Conclusion: PRP provides similar pain reduction compared with steroid injection, with the additional advantage of potential regenerative effects. Further studies are warranted to evaluate structural regeneration